Petrografia dos granitos do maciço Santa Cruz, província estanífera de Rondônia - Branco, Vítor Xatara [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The Santa Cruz massif is located about 10 km northeast of the Bom Futuro mine, and occurs in the domain of the Younger Granites of Rondônia (998-974 Ma). The present work consisted in the petrographic study of samples of granite bodies of this massif, in order to better characterize it, since there are few works on this massif. The petrography revealed the existence of granitic facies such as alkali-feldspar granites, biotite sienogranites, hornblende-biotite alkali-feldspar granites and hornblende-biotite sienogranites, distributed in two distinctly textured groups: a group of equigranular granites, usually of a pinkish color, and another group of fine-grained porphyritic granites, commonly gray in color. The modal composition of these samples shows predominance of alkali feldspar, quartz and, in a smaller quantity, plagioclase, besides biotite, hornblende and sodium amphibole as mafic (main mafic biotite). The accessory phase is represented by zircon, chlorite, apatite, muscovite, alanite and opaque. It is possible to identify mimerchytic fabric and cross-hatch twinning, Carlsbad twinning and polysynthetic twinning, in the feldspar and plagioclase crystals. In addition, alteration features are recognized, evidencing sodium, potassium and argillic alteration acting on these rocks. It is common to find in the Younger Granites of Rondônia biotite granites associated with hornblende-biotite granites, in the São Carlos and Massangana massifs, but there was still no record of granites with sodium amphibole in other massifs. The presence of peralkaline granite in the Santa Cruz massif allows to recognize the existence of two late and chemically distinct subsuites, one of metaluminous and peralcaline nature, and another of peraluminous nature. Rocks with similar configuration occur in the province of Jos, Nigeria, and allow a good correlation with the magmatism of the Younger Granites of Rondônia

O maciço Santa Cruz está localizado a cerca de 10 km a nordeste da mina Bom Futuro, e ocorre no domínio da Suíte Intrusiva Granitos Últimos de Rondônia (998-974 Ma). O presente trabalho consistiu no estudo petrográfico de amostras de corpos graníticos desse maciço, afim de melhor caracterizá-lo, uma vez que existem poucos trabalhos sobre esse maciço. A petrografia revelou a existência de fácies de álcali-feldspato granito, biotita sienogranito, hornblenda-biotita álcali-feldspato granito e hornblenda-biotita sienogranito, distribuídos em dois grupos texturalmente distintos: um grupo de granitos equigranulares, usualmente de coloração rósea, e outro grupo de granitos porfiríticos de matriz fina, comumente de coloração cinza. A composição modal dessas amostras revela predominância de feldspato alcalino, quartzo e, em menor quantidade, plagioclásio, além de biotita, hornblenda e anfibólio sódico como máficos (biotita máfico principal). A fase acessória é representada por zircão, clorita, apatita, muscovita, alanita e opacos. Além disso, são reconhecidas feições de alteração, evidenciando alteração sódica, potássica e argílica atuantes sobre essas rochas. Encontra-se na Suíte Intrusiva Granitos Últimos de Rondônia biotita granitos associados a hornblenda-biotita granitos, nos maciços São Carlos e Massangana, porém ainda não se tinha registro de granitos com anfibólio sódico na moda em outros maciços. A presença de granito peralcalino no maciço Santa Cruz permite reconhecer a existência de duas subsuítes tardias e quimicamente distintas, uma de natureza metaluminosa e peralcalina, e outra de natureza peraluminosa. Rochas com semelhante configuração ocorrem na província de Jos, na Nigéria, e permitem uma boa correlação com o magmatismo da Suíte Intrusiva Granitos Últimos de Rondônia
Keywords: Petrologia; Granito; Fácies (Geologia); Geologia; Rochas; Rondonia